Saliva and urine metabolic profiling reveals altered amino acid and energy metabolism in male farmers exposed to pesticides in Madhya Pradesh State, India. (July 2019) - Ch, Ratnasekhar; Singh, Amit Kumar; Pathak, Manoj Kumar; Singh, Amarnath; Kesavachandran, Chandrasekharan Nair; Bihari, Vipin; Mudiam, Mohana Krishna Reddy
Abstract: Globally, the human population is exposed to low doses of pesticides due to its extensive use in agriculture. The chronic exposure to pesticides can lead to cancer, depression, anxiety, Parkinson's and Alzheimer's diseases etc. Here, we have made an attempt to use mass spectrometry based metabolomics to investigate the metabolic perturbations induced by the pesticides in the urine and saliva samples of farmers from the Madhya Pradesh State of India. The study was aimed to establish non-invasive matrices like urine and saliva as alternative diagnostic matrices to the occupational exposure studies. Saliva and urine samples were collected from 51 pesticides applicators and acquired metabolic profiles of urine and saliva samples using gas chromatography-mass spectrometry (GC-MS). Multivariate pattern recognition and pathway analysis were used to analyze and interpret the data. Investigation of endogenous metabolic profiles revealed remarkable discrimination in both saliva and urine samples of the exposed population strongly suggesting the changes in metabolic composition within the identified metabolites (for urine samples: accuracy 0.9766, R 2 = 0.9130, Q 2 = 0.8703; for saliva samples, an accuracy of 0.9961, R 2 = 0.9698, Q 2 = 0.9637). Thirteen metabolites of urine samples and sixteen metabolites of saliva samples were identified as differential metabolites specific to pesticide exposure. Pathway analysis of differential metabolites revealed that amino acid metabolism, energy metabolism (glycolysis and TCA cycle) and glutathione metabolism (oxidative stress) were found to affect in pesticide exposed population. The present study suggested that GC-MS based metabolomics can help to reveal the metabolic perturbations in human population after pesticides exposure. Highlights: Saliva and urine metabolomics study to assess the pesticide exposure in the farmers. Metabolomics has shown the alternations in various metabolic pathways. Glycolysis, TCA cycle and amino acid metabolism altered in the exposed population.